Evaluation of The Threshold for Taxable Enterprises in Indonesia: Impact and Proposal Using Institutional Theory - Afriyanto, Alan; Hidayah, Siti Noor Aini (Universitas Muhammadiyah Yogyakarta, 2025)
This research was conducted to analyze the impact of implementing the Taxable Entrepreneurs (PKP) threshold of IDR4,800,000,000.00. The novelty of this research is using institutional theory, proposing new Value Added Tax (VAT) collection mechanism, and calculating the potential VAT from the threshold revision. This research is qualitative research with a case study approach. This study uses an interactive analysis model. Data was collected in three ways, namely in-depth interviews, qualitative observation, and documentation studies. The Sub-Directorate of VAT Regulations, Services and Other Indirect Taxes was chosen as the research site. There were six sources in this study, namely the Head of Sub-Directorate, Head of Section, Strategic Account Representative, Regional Account Representative, and lecturers. The findings in this research are that the high threshold results in the VAT tax base being eroded; often misused to avoid taxes; and reduced the amount of Tax Invoice data for supervisory activities. Based on research findings, policy makers in the Directorate General of Taxes (DGT) should immediately revise PMK-197/2013 and PMK-164/2023 by lowering the threshold to IDR600,000,000.00 and creating a new VAT mechanism, namely with a margin scheme of 1.1%.